Converse, Charles Albert. Letter to Family ("Dottie and Kiddies"), Manchester, England. November 25, 1939. - Converse, Charles Albert (Valdosta State University Archives and Special Collections, 2018, 1939)
I received a very great and extremely Disappointing piece of news this morning but we mustn't get too down hearted. I have been trans- ferred to Manchester. I could hardly believe it as you can readily imagine. Never-theless there it is and I have to proceed there in January on the arrival of my successor, Palmer, who is now at Saigon, French Indo China. A good break for him and I suppose that he deserves it after serving there. I have had along talk with Mr Erhardt and also Herschel and they don't feel that it would be wise to try and do anything about it. Both seem to feel that it is a excellent opportunity for me to do some excellent work and that the assignment will not be a long one.
Converse, Charles Albert. Letter to Family ("Dottie and Kiddies"), Manchester, England. November 25, 1939. Valdosta State University Archives and Special Collections, Charles Albert Converse Papers, 1939-1940 (ms158er1-011). http://hdl.handle.net/10428/3029.| Typewritten letter, 4 pages, with a handwritten note on page leaf.
Keywords: Converse, Charles Albert (1904-1940); Diplomatic and consular service; United States. Embassy (Great Britain); Letters.; World War (1939-1945)